Nilai-nilai Pendidikan Aqidah dalam Prespektif QS. Al-Baqarah Ayat 186 - Padjadjaran Lagatari, Muhammad Rajaffawwaz; Helmi Aziz; Enoh (UNISBA Press, 2024)
Abstract. Education problems in Indonesia involve phenomena such as bullying and LGBTQ understanding. One of the problems is in the aqidah, as explained in Al-Baqarah verse 186. This verse contains the values of Aqidah Education that can be applied in the learning process. The purpose of this study is to find out the interpretation of the mufassir about QS. Al-Baqarah verse 186, the essence of Q.S Al-Baqarah Verse 186, knowing the concept of Aqidah education according to experts, knowing the values of aqidah education in Q.S Al-Baqarah Verse 186 and the concept and values of Aqidah education. This research uses a qualitative approach method, with primary data from the Quran and Hadith.The results of the study showed: First, the mufassir has similarities in interpreting Q.S Al-Baqarah verse 186, that Allah is close to His servants who believe, Allah always grants His servant's prayers and always hopes that his prayers are answered by Allah and always carry out His commands and fulfill His prohibitions as a condition for the fulfillment of prayers. Second, the essence that can be taken is: Allah SWT is close to His servant who believes, Allah SWT grants His servant's prayer, Carries out His commandments and fulfills His prohibitions as a condition for answered prayers. Third, the values of Aqidah Education in Q.S Al-Baqarah verse 186 are: the value of monotheism, among others, Allah is close to His servants who believe, believe in Allah's worship with prayer and pray only to Allah and not to others. The value of piety, among others, Believing that the prayer answered by Allah is the best, Allah never wastes the prayers of His servants and Believes in Allah. Abstrak. Permasalahan pendidikan di Indonesia melibatkan fenomena seperti bullying dan paham LGBTQ. Salah satu permasalahannya adalah dalam aqidah, seperti yang dijelaskan dalam Al-Baqarah ayat 186. Ayat ini mengandung nilai-nilai Pendidikan Aqidah yang dapat diterapkan dalam proses pembelajaran. Tujuan penelitian ini adalah untuk mengetahui penafsiran para mufassir tentang QS. Al-Baqarah ayat 186, esensi Q.S Al-Baqarah Ayat 186, mengetahui konsep pendidikan Aqidah menurut para ahli, mengetahui nilai-nilai pendidikan aqidah dalam Q.S Al-Baqarah Ayat 186 serta konsep dan nilai-nilai pendidikan Aqidah. Penelitian ini menggunakan metode pendekatan kualitatif, dengan data primer dari Al-Quran dan Hadits. Hasil dari penelitian menunjukkan: Pertama, para mufassir memiliki kesamaan dalam menafsirkan Q.S Al-Baqarah ayat 186, bahwa Allah dekat dengan hamba-hamba-Nya yang beriman, Allah selalu mengabulkan do’a hamba-Nya dan selalu berharap doanya dikabulkan oleh Allah dan senantiasa menjalankan perintah-Nya serta menjahui larangan-Nya sebagai syarat dikabulkannya doa. Kedua, esensi yang dapat diambil yaitu: Allah SWT dekat dengan hamba-Nya yang beriman, Allah SWT mengabulkan doa hamba-Nya, Menjalankan perintah-Nya dan menjahui larangan-Nya sebagai syarat terkabulkanya doa. Ketiga, nilai-nilai Pendidikan Aqidah dalam Q.S Al-Baqarah ayat 186 yaitu: nilai ketauhidan, diantaranya, Allah dekat dengan hamba-Nya yang beriman, yakin akan ibadah Allah dengan do’a dan Berdoa hanya kepada Allah tidak kepada yang lain. Nilai ketakwaan, diantaranya, Yakin akan doa yang dikabulkan Allah itu yang terbaik, Allah tidak pernah menyia-nyiakan doa hamba-Nya dan Percaya kepada Allah.